Preparation and thermal stability of doped TiO2 composite membranes by the sol-gel process - Bae, DS; Han, KS; Choi, SH (ELSEVIER SCIENCE BV, 1998)
Supported TiO2, composite membranes doped with various elements (Fe2O3, CeO2, Pt) were synthesized by the sol-gel process. The average particle size of the doped TiO2 sol was below 15 nm and well dispersed in the solution. XPS results show the additive to be continuously and homogeneously dispersed in the TiO, membrane. It was observed that the TiO, composite membranes doped with Fe2O3, CeO2, and Pt had higher heat resistance than that of the pure TiO2 composite membrane. The effect of sintering on the change of the mean particle diameter of the several membranes was decreased in the following order: Fe2O3 > CeO2 greater than or equal to Pt. It was observed that the doped TiO2 composite membranes showed a crack-free and homogeneous microstructure as well as a narrow particle size distribution up to above 650 degrees C. (C) 1998 Elsevier Science B.V. All rights reserved.
Keywords: ZIRCONIA MEMBRANES; ALUMINA MEMBRANES; TITANIA